The efficiency of an improved seismic vulnerability index under strong ground motions. (February 2020) - Kassem, Moustafa Moufid; Mohamed Nazri, Fadzli; Noroozinejad Farsangi, Ehsan
Abstract: This paper examines the seismic performance of a Hospital Building damaged during the Ranau earthquake in Malaysia of intensity level (VIII), through an improved empirical seismic vulnerability index (SVI). The research aims at reducing the limitations and the uncertainties associated with the GNDT and the EMS approaches related to RC buildings, which can possibly be resolved by implementing the analytical techniques via applying nonlinear parametric analysis. Nonlinear time-history analyses were performed by incorporating an array of strong ground motions divided between far-field and near-field sets to assess the influence of each category on the SVI values and then comparing with SVI values obtained from the nonlinear static analysis (NSA). For a better comparison, the results are depicted in terms of collapse fragility curves for the modeled parameters. The proposed approach has been verified through observational fragility curves after Ranau earthquake. Whereas, the obtained SVI values were similar for the near-field and far-field, but with different collapse intensities and mean damage grades.